The Scanning Electron Microscope (SEM) assessment system using the autoregressive (AR) technique - Sim, KS; Chuah, HT; Kamel, NS (2005)
In this paper, a novel real-time SNR estimator is proposed. The technique is based on the Autoregressive model and can be embedded onto SEM imaging system for image assessment. The AR based estimator is robust and effective in estimating the noise second order statistics which is required for Wiener filtering process. The AR wiener filter is then embedded onto the frame grabber card to do real-time SEM noise removal. The AR-based method is compared with the Simple method-wiener filter as well as First-order interpolation-wiener filter. In the most testing cases, the AR-wiener filter outperforms the rest of the systems.